Selective stalling of human translation through small-molecule engagement of the ribosome nascent chain. - Nathanael G Lintner; Kim F McClure; Donna Petersen; Allyn T Londregan; David W Piotrowski; Liuqing Wei; Jun Xiao; Michael Bolt; Paula M Loria; Bruce Maguire; Kieran F Geoghegan; Austin Huang; et al. (PLoS Biology, 2017)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a key role in regulating the levels of plasma low-density lipoprotein cholesterol (LDL-C). Here, we demonstrate that the compound PF-06446846 inhibits translation of PCSK9 by inducing the ribosome to stall around codon 34, mediated by the sequence of the nascent chain within the exit tunnel. We further show that PF-06446846 reduces plasma PCSK9 and total cholesterol levels in rats following oral dosing. Using ribosome profiling, we demonstrate that PF-06446846 is highly selective for the inhibition of PCSK9 translation. The mechanism of action employed by PF-06446846 reveals a previously unexpected tunability of the human ribosome that allows small molecules to specifically block translation of individual transcripts.